Southern Green Stink Bug, Nezara viridula (Linnaeus) (Insecta: Hemiptera: Pentatomidae) - Jason M. Squitier (EDIS, 2011)
Revised! EENY-016, a 5-page illustrated fact sheet by Jason M. Squitier, is part of the Featured Creatures collection. It describes this shield-shaped polyphagous feeder that attacks many important food crops — distribution, description, life cycle, damage action threshold, and management. Includes references. Published by the UF Department of Entomology and Nematology, October 2010.